2017
DOI: 10.1016/j.atmosenv.2016.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of gravestone decay and air quality 1960–2010

Abstract: Evaluation of spatial and temporal variability in surface recession of lead-lettered Carrara marble gravestones provides a quantitative measure of acid flux to the stone surfaces and is closely related to local land use and air quality. Correlation of stone decay, land use, and air quality for the period after 1960 when reliable estimates of atmospheric pollution are available is evaluated. Gravestone decay and SO2 measurements are interpolated spatially using deterministic and geostatistical techniques. A gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The microstructure of samples were observed by a scanning electron microscopy (SEM, FEI SIRION-100, 5.0 kV of accelerating voltage and 8.0 mm of working distance). The phase constituent of the samples were detected by an X-ray diffraction (XRD, AXS D8 ADVANCE, scan range 2θ = 10-80°).…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The microstructure of samples were observed by a scanning electron microscopy (SEM, FEI SIRION-100, 5.0 kV of accelerating voltage and 8.0 mm of working distance). The phase constituent of the samples were detected by an X-ray diffraction (XRD, AXS D8 ADVANCE, scan range 2θ = 10-80°).…”
Section: Characterizationmentioning
confidence: 99%
“…It is a weathering product of calcareous stone under the attack of sulfur oxide pollutants in the air [2] . The formation of gypsum weathering layer is often accompanied with appearance alteration [3] , surface dissolution [4] and structure disruption [5] of the rock relics. The removal of this kind of harmful gypsum layer is thus believed to be necessary [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…Inkpen et al, 2017) have examined the rate of gravestone weathering to trace atmospheric levels of sulphur, finding the highest levels in industrial locations, such as in Swansea compared with Birmingham, Portsmouth, and Oxford, with rural and suburban sites having very low sulphur concentrations. Moreover, the research by Mooers et al (2017) has indicated the increased deposition efficiency of SO 2 on Carrara marble gravestones since 1980 due to oxidation reactions with ammonia. Such chemical reactions involve complex interactions that are seldom conveyed in the contemporary literature, even though rock weathering can be construed as a complex system.…”
Section: Weathering Researchmentioning
confidence: 99%
“…As with other cultural monuments, including churches, these stone monuments have become part of cultural heritage studies by weathering scientists examining stone decay in burial settings as well as in other settings on a comparative basis in studies of air pollution impacting the conservation of gravestones (e.g. Cooke et al, 1995; Mooers et al, 2017). One of the greatest contributions of such studies has been dates inscribed into headstones that enable the researcher to quantify cross-temporal change at scales up to the centennial in older churchyards.…”
Section: Landscape Change As ‘Necrogeography’mentioning
confidence: 99%
“…Therefore, it is not always possible to measure the surface recession rate in natural rock outcrops (Moses et al, 2014). Therefore, the determination to calculate the rock weathering rates of tombstones or ancient buildings built with rock bricks, and their artificial cutting time, has become the main approach for calculating the weathering rate of rocks on a decadal or centennial time scale (Takahashi et al, 1994;Cooke et al, 1995;Robinson and Williams, 1999;Williams and Robinson, 2000;Johnson et al, 2010;Morgan, 2016;Waragai, 2016;Mooers et al, 2017). In fact, relatively few field observations have been made on the rate at which weathering occurs on natural rock outcrops (Turkington and Paradise, 2005).…”
Section: Introductionmentioning
confidence: 99%